Radar and communication spectrum sharing - Blunt, Shannon D.; Perrins, Erik Samuel, 1973- (IET radar, sonar, navigation and avionics series., 2018)
The book, consisting of 23 chapters, studies radar and communication spectrum sharing by looking at systems engineering perspectives, addressing interference and considering radar/communication co-design.